Comparison of a rapid albuterol pathway with a standard pathway for the treatment of children with a moderate to severe asthma exacerbation in the emergency department. (4th March 2018) - Wilkinson, Matthew; King, Ben; Iyer, Sujit; Higginbotham, Eric; Wallace, Anna; Hovinga, Collin; Allen, Coburn
ABSTRACT: Objective : The objective of this study was to determine if a rapid albuterol delivery pathway with a breath-enhanced nebulizer can reduce emergency department (ED) length of stay (LOS), while maintaining admission rates and side effects, when compared to a traditional asthma pathway with a standard jet nebulizer. Methods : Children aged 3–18 presenting to a large urban pediatric ED for asthma were enrolled if they were determined by pediatric asthma score to have a moderate to severe exacerbation. Subjects were randomized to either a standard treatment arm where they received up to 2 continuous albuterol nebulizations, or a rapid albuterol arm where they received up to 4 rapid albuterol treatments with a breath-enhanced nebulizer, depending on severity scoring. The primary endpoint was ED LOS from enrollment until disposition decision. Asthma scores, albuterol dose, side effects, and return visits were also recorded. Results : A total of 50 subjects were enrolled (25 in each arm). The study LOS was shorter in the rapid albuterol group (118 vs. 163 minutes, p = 0.0002). When total ED LOS was analyzed, the difference was no longer statistically significant (192 vs. 203 minutes, p = 0.65). There were no statistically significant differences with respect to admission rates, asthma score changes, side effects, or return visits. Conclusion : A rapid albuterol treatment pathway that utilizes a breath-enhanced nebulizer is an effective alternative to traditional pathways that utilize continuous nebulizations for children with moderate to severe asthma exacerbations in the ED.